Cybercrime in virtual spaces: An overview of the law in Indonesia - Zulfan (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
The Internet has the potential to overcome national barriers and facilitate global dissemination of information. Although its benefits are numerous, it also has detrimental consequences that could disrupt society. Engaging in cybercrime is typically required only to create a substantial number of blogs, accounts, applications, programs, and websites on various social and mass media platforms for illicit purposes. Examples of unlawful activities include, but are not limited to, fraud, data theft, unauthorized use of credit cards, distribution of inappropriate content, online gambling, and prostitution, as well as hate speech and extremist or terrorist activities. To address the issue of virtual space crime, the government enacted Law No. 19 of 2016, which amended Law No. 11 of 2008, with respect to information and electronic transactions. However, it is important to recognize that not all people who use the internet have a comprehensive understanding of the legal framework. Consequently, government, employers, and institutions involved in information and communication technology are responsible for educating the public about the law to reduce the incidence of criminal activity in virtual spaces.